Study on lyotropic liquid crystals doped with DNA. Issue 1 (2nd May 2016) - Furue, H.; Segawa, T.; Sugisaki, I.; Iwabata, K.; Sakaguchi, K.
ABSTRACT: We focus on a lyotropic LC in the water system similar to the living body, and we have investigated the behavior of deoxyribonucleic acid (DNA) molecules in the DNA-doped lyotropic LC. As a result, in the concentration of DNA doped in this research, the mesomorphic property of LC does not change. On the other hand, the microscopic texture becomes disturbed and the domain breaks down by DNA doping. As a result of ion density measurement, the ion current peaks can be obtained by DNA doping, and thus, DNA molecules can behave as ion careers in LC medium.